Assessing the effect of late-season fertilization on Holm oak plant quality: insights from morpho–nutritional characterizations and water relations parameters - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER (New Forests, 2014)
Forest restoration projects with Holm oak (Quercus ilex) have had limited success, mostly due to water stress after planting and poor plant quality. Recent studies indicated that large and nutrient rich plants perform better in Mediterranean areas, sug- gesting that late-season fertilization may improve plant quality and field performance. The purpose of this study was to assess the effect of late-season fertilization on the quality of Holm oak seedlings, as determined by morphological, nutritional, and water relations analyses. We grew Holm oak nursery seedlings under 5 different late-season fertilization regimes and then analyzed morphological characteristics, nutritional status, and water relations parameters of the fertilization groups at the end of the nursery period. We also analyzed the effect of fertilization on nutritional status by use of vector nomograms. Our results indicated that late-season NPK fertilization improved shoot and root growth, and the overall nutritional status of seedlings. The lack of late-season fertilization leads to nutrient deficiency in plants, whilst the application of imbalanced fertilization treatments may trigger nutrient luxury consumption and nutrient dilution, pointing out the importance of NPK proportions in the fertilizer. Moreover, late-season fertilization with nitrogen might improve the drought resistance of seedling by enhancing their osmotic adjustment.
Keywords: Autumn fertilization; Nursery culture; Nutrient loading; osmotic adjustment; Quercus ilex; Vector analysis

Litter production in Holm oak trees subjected to different pruning intensities in Mediterranean dehesas - Andivia, Enrique; VÁZQUEZ-PIQUÉ, JAVIER; FERNÁNDEZ, MANUEL; Alejano, Reyes (Agroforestry systems, 2012)
Litterfall is a key process in forests which is sensitive to climatic conditions like precipitation and temperature, and management practices. Therefore, knowledge about litterfall patterns and its associated variables is important for the conservation of Mediterranean ecosystems under conditions of climate change. We aimed to quantify the temporal pattern of litterfall and to investigate the inﬂuence of abiotic variables and pruning on litter production. Litterfall was collected at monthly intervals for 2 years in trees subjected to different pruning intensities in two locations. The effect of pruning, abiotic variables and tree size on litter production was analyzed using a mathematical model. Leaf fall was strongly seasonal with a peak occurring in the wettest month of the year in this area. The variability in leaf fall was mainly related to rainfall and soil water in 2 years and locations. Pruning reduced the amount of litter production during the ﬁrst year following this practice, and might have negative effect on soil fertility and crop productivity in dehesas ecosystems.
Keywords: á agroforestry systems; á litterfall á; agroforestry systems; climate change; climate change á management; litterfall; management; pruning; Quercus ilex; quercus ilex á pruning

Seasonal evolution of water status after outplanting of two provenances of Holm oak nursery seedlings - Andivia, Enrique; Carevic, Felipe; FERNÁNDEZ, MANUEL; Alejano, Reyes; VÁZQUEZ-PIQUÉ, JAVIER; TAPIAS, RAÚL (New Forests, 2012)
Forest restoration programs using Holm oak (Quercus ilex ssp. ballota [Desf.] Samp.) have had limited success. The effect of plant provenance on plantation success is uncertain, although some previous studies suggest that some provenances may be better able to tolerate stress. We studied the tolerance to drought in seedlings from two Spanish provenances of Holm oak before and after outplanting. One provenance was from a continental climate with cold winters (GR) and the other was from a xeric climate (HU). Seedlings were subjected to a water stress test in the nursery during the summer and survival was visually assessed after 2 weeks. In addition, 35 healthy seedlings of each provenance that were not subjected to the water stress tests were used for outplanting experiment. In these plants the seasonal changes in water potential at dawn (W), speciﬁc leaf area (SLA), cuticular transpiration (Ec ), and loss of xylem hydraulic conductance of twigs (PLC) were measured over 18 months. After the water stress test in summer, mortality was 44.3 % for GR seedlings and 12.6 % for HU seedlings. In addition there were differences between the two provenances in plant water status after planting. The HU provenance had a better water status and was more water conservative in the summer (higher W, lower Ec , lower PLC), but not in the winter. The different drought tolerance and water relations parameters of these two provenances indicate that provenance should be considered in forest restoration and conservation programs involving Holm oak.
Keywords: Adaptation; Drought; Field performance; Physiological traits; water stress

Autumn fertilization of Quercus ilex ssp. ballota (Desf.) Samp. nursery seedlings: effects on morpho-physiology and field performance - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER (Annals of Forest Science, 2011)
& Background The Holm oak (Quercus ilex ssp. ballota [Desf.] Samp.) is an evergreen tree widely distributed in the western Mediterranean Basin. Forest restoration programs using this species have enjoyed only limited success, and knowledge concerning the effect of fertilization on plant quality and post-transplantation response is sparse. & Methods We assessed the effect of autumn fertilization using different doses of nitrogen, phosphorus, and potassium (70.0 mg N, 30.5 mg P and 58.1 mg K during the growing phase for all plants; and 30.0 vs 1.5 mg N, 13.1 vs 0.3 mg P and 24.9 vs 0.5 mg K during the hardening phase, depending on the fertilization treatment) on the seedling characteristics and field performance of Holm oak. & Results and Conclusions Autumn fertilization, especially with N, did not decrease plant quality but improved overall growth, root growth capacity, cold hardiness, and the nutritional content of nursery-grown seedlings. However, autumn fertilization had only a small effect on field performance, which was affected only by K fertilization, probably because of the adequate N and P nutrient status of all the plants and the mild weather conditions of the field plot. In our site, which had a mild winter climate, late autumn out-planting was more successful than was midwinter out-planting.
Keywords: Cold hardiness; Field performance; Holm oak; Nursery fertilization; Nutritional status

Autumn fertilization with nitrogen improves nutritional status, cold hardiness and the oxidative stress response of Holm oak (Quercus ilex ssp. ballota [Desf.] Samp) nursery seedlings - Andivia, Enrique; Márquez-García, Belén; VÁZQUEZ-PIQUÉ, JAVIER; Córdoba, Francisco; FERNÁNDEZ, MANUEL (Trees, 2011)
Holm oak (Quercus ilex ssp. ballota [Desf.] Samp) is one of the most important species in forest communities of the western Mediterranean Basin, but is very vulnerable to environmental stress during the ﬁrst years of its life. In particular, summer drought and winter frosts limit the distribution, survival, and growth of Holm oak. These two stress factors can lead to plasmolysis and/or oxidative stress. We hypothesized that autumn fertilization with nitrogen (N) can improve plant tolerance to these abiotic stress factors and improve plant quality and therefore reforestation success. A 12-week autumn application of 30 or 60 mg N (plus 70 mg N applied to both treatments during the previous 28 weeks in the nursery, i.e. 100 and 130 mg N in total, respectively) improved overall growth, root growth capacity, frost tolerance, and nutritional status of plants relative to plants given 0.0 and 1.5 mg autumnal N, and had no negative effect on seedling response to water stress. A very small increment in N doses during the autumn (1.5 vs. 0.0 mg N) improved some morphological parameters, such as stem diameter (D) and shoot dry weight, and physiological parameters, such as total antioxidant activity. The highest autumnal N dose (60 mg) increased leaf nutrient content without decreasing the concentration, but had a tendency to reduce frost tolerance relative to seedlings given a lower autumnal N dose (30 mg).
Keywords: Frost tolerance; Holm oak; Mineral nutrients; Oxidative stress; water stress

Two provenances of Quercus ilex ssp. ballota (Desf) Samp. nursery seedlings have different response to frost tolerance and autumn fertilization - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER; Alejano, Reyes (European Journal of Forest Research, 2011)
Despite evidences that Holm oak has a high plasticity and great adaptability, there is limited or contradictory knowledge of the morphological and physiological variability of this species. Holm oak has been widely used for reforestation projects in Mediterranean areas, but has frequently shown poor ﬁeld performance. We hypothesized that Holm oak has inter-population differences in physiological responses to abiotic stressors that could affect reforestation success. The inﬂuence of nursery culture on the characteristics of Holm oaks from different provenances has not been explored in depth. Thus, we studied the effect of nursery autumn fertilization on morphological traits, frost tolerance, root growth potential, and nutritional status of two Spanish provenances of Holm oak, La Alcarria (a region with inland Mediterranean climate) and Sierra Morena Occidental (a region with a warm coastal Mediterranean climate). There were signiﬁcant differences between the provenances in frost tolerance, biomass allocation, and leaf nutrient content, suggesting a role of genetic factors. The leaves of seedlings from La Alcarria had less visual damage at -12C than seedlings from the warmer provenance (45% vs. 92%). Seedlings from La Alcarria, compared to those from Sierra Morena, had higher leaf P concentration (0.17% vs. 0.15%), greater stem diameter (3.1 mm vs. 2.7 mm), lower shoot-to-root dry mass ratio (0.46 vs. 0.53), and lower slenderness (4.03 vs. 5.31). For both provenances, N autumn fertilization improved growth, root growth potential, cold hardiness, and nutritional status of seedlings. We suggest that forest reforestation programs should consider to a greater extent Holm oak provenances and their tolerances to different abiotic stressors.
Keywords: á autumn fertilization; á reforestation á; Adaptation; adaptation á cold hardiness; Autumn fertilization; Cold hardiness; Holm oak; holm oak á provenance; provenance; Reforestation

Nutrients return from leaves and litterfall in a mediterranean cork oak (Quercus suber L.) forest in southwestern Spain - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER; González-Pérez, Aranzazu; TAPIAS, RAÚL (European Journal of Forest Research, 2010)
The knowledge of the cycle of nutrients is fundamental for the correct comprehension of the tree–soil relationship and for an adequate forest management. In order to analyse the nutrients return from leaves and litterfall in a Mediterranean cork oak forest in southwestern Spain, 12 trees were randomly selected and litterfall collected for 2 years. Samples were taken monthly and separated in different fractions (leaves, twigs, catkins, acorns and mis- cellaneous), then leaves nutrients were analyzed. Simulta- neously, we analyzed the nutrient content of living leaves from the same trees in each season during 1 year. The ana- lyzed nutrients were C, N, P, K, Ca, Mg, Fe, Mn, S, Cu, Zn and Mo. Annual patterns of each nutrient in fallen leaves were characterized and compared with seasonal values of these nutrients in living leaves. Leaves fall has two annual maximum, first and most important in spring around April coinciding with renewal of foliar cover and second around October. Main concentration patterns of N, P and K are related with phenological patterns, in consequence mini- mumconcentration in leaves fall were obtained in periods of growing and maximum litterfall. Concentrations of Ca, Fe and Mn increase with the age of the leaves and maximum concentrations were obtained before periods of maximum litterfall while concentrations of Cu, Mo and Mg stay stable. Communicated by A. Merino. A. Gonza This article belongs to the special issue ‘‘Plant–soil relationships in Southern European forests’’. E. Andivia (&)  M. Ferna ´lez-Pe Department of Forest Sciences, University of Huelva, Ctra. Palos–La Ra ´rez  R. Tapias Huelva, Spain e-mail: enrique.andivia@dcaf.uhu.es ´ndez  J. Va ´zquez-Pique ´  ´bida, s/n. 21819 Palos de la Frontera, Seasonal analysis of nutrients in living leaves collected from the same trees in four different periods of the year allowed to corroborate the patterns of leaves fall and the probable osmotic function of K.
Keywords: litterfall; Nutrients cycling; Nutrients return; Quercus suber